2014
DOI: 10.1007/s12185-014-1641-8
|View full text |Cite
|
Sign up to set email alerts
|

Aging of the hematopoietic stem cells niche

Abstract: Homeostasis of the hematopoietic system has its roots in the maintenance of hematopoietic stem cells (HSCs) in the bone marrow (BM). HSCs change both phenotypically and functionally with physiological age. The alterations noted in aged HSCs are thought to be a consequence of both cell-intrinsic and extrinsic changes. We review here the age-related changes that the BM microenvironment exerts on HSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 98 publications
(103 reference statements)
0
16
0
Order By: Relevance
“…Such alterations in the aged BM niche have led to the speculation that these changes might also play a role in the development of haematological malignancies [15], which are often age-related; this is supported by the observation that a pre-leukaemic cell line showed preferential growth in aged BM [28]. In another study by the same authors, they showed that transplantation of transformed HSC clones developed preferentially in the aged BM microenvironment in comparison to the young BM niche [29].…”
Section: The Aged Bone Marrow Nichementioning
confidence: 96%
“…Such alterations in the aged BM niche have led to the speculation that these changes might also play a role in the development of haematological malignancies [15], which are often age-related; this is supported by the observation that a pre-leukaemic cell line showed preferential growth in aged BM [28]. In another study by the same authors, they showed that transplantation of transformed HSC clones developed preferentially in the aged BM microenvironment in comparison to the young BM niche [29].…”
Section: The Aged Bone Marrow Nichementioning
confidence: 96%
“…The alterations noted in aged hematopoietic stem cells were until recently thought to be a consequence of cell-intrinsic modifications (65,66). Nevertheless, new data the important role of multiple extrinsic factors in driving hematopoietic stem cell aging (67). Zhou and colleagues investigated the importance of adipocyte-derived stem cell factor in genotoxic insults in the bone marrow (19).…”
Section: Perspectives / Future Directionsmentioning
confidence: 99%
“…* Atsushi Hirao ahirao@staff.kanazawa-u.ac.jp 1 Division of Molecular Genetics, Cancer Research Institute, Kanazawa University, Kanazawa, Ishikawa 920-1192, Japan ability of regulatory transcription machinery proteins to access the chromatin of genomic DNA, thereby controlling gene expression. In particular, Polycomb group (PcG) proteins contribute to self-renewal of HSCs by repressing genes involved in differentiation.…”
Section: Epigenetic and Metabolic Regulation In Hematopoiesis/ Leukemmentioning
confidence: 99%
“…Acetylation, methylation, and phosphorylation of histones change the Hematopoietic stem cells (HSCs) are defined as cells that have the ability to perpetuate undifferentiated status through self-renewal and to develop into mature cells through differentiation. Fine-tuning of self-renewal and differentiation programs, mediated by cooperative networks of intrinsic and extrinsic factors, contributes to stem cell homeostasis in vivo [1,2]. Accumulating evidence has revealed the presence of "stemness" signals; that is, molecules and signaling pathways that play critical roles in maintaining the undifferentiated properties of HSCs.…”
mentioning
confidence: 99%